Inhibiting Factors and Educational Policy Efforts in Increasing Access to Education in Remote Areas - Lintang, Retno; Pambudi, Argo (Universitas Negeri Yogyakarta, 2025)
Education policy plays an important role in increasing access to education in remote areas. This study explores various policy strategies that have been implemented to address challenges related to access to education in remote areas, with a focus on their effectiveness and impact. The research method uses descriptive analysis by collecting data from various sources related to education policy and evaluating the implementation of these policies. The research results show that the success of education policies to increase access in remote areas is strongly influenced by cross-sectoral coordination, local community participation and reasonable resource allocation. The importance of this research is the need for greater attention to designing inclusive and sustainable education policies to achieve the goal of equitable education in all regions, including remote areas.